Thinking about the future – data on adolescent patients with a subcutaneous ICD. (25th November 2020) - Willy, K; Reinke, F; Rath, B; Boegeholz, N; Wolfes, J; Frommeyer, G; Eckardt, L
Abstract: Background: Implantable cardioverter-defibrillator (ICD) systems are established for the prevention of sudden cardiac death. Long-term data on ICD function in children and adolescents is rare and has suggested higher rates of lead failure as well as oversensing, both leading to inappropriate therapy. The present study displays a long-term single-center follow-up of young patients having received an S-ICD. Methods and results: The present study represents a single-center experience of patients younger than 25 years who received an S-ICD (n=49). Follow-up data included regular in-house follow-up as well as unscheduled hospitalisations in our center. Mean age at implantation was 19.2±4.1 years and 33 patients (67.4%) were male. In 21 patients (42.9%) electrical heart disease or idiopathic ventricular fibrillation represented the underlying condition of ICD implantation. 15 patients suffered from HCM (30.6%). Median follow-up duration was 2 years. No patient died during the observation period. Appropriate shocks occurred in 7 patients (14.3%). Inappropriate shock delivery was recorded in 6 patients (12.3%). T-wave oversensing was the main cause for inappropriate shock delivery (5/6 patients), in the other patient myopotentials were the reason for inappropriate therapy. In one patient, operative refixation of the subcutaneous lead was necessary due to hypermobility leading to oversensing. After modification of the sensing vector as well as activation of the SMART pass filter no further oversensing episodes occurred in any patient. Conclusion: ICD therapy in children and adolescents is effective for prevention of sudden cardiac death. Every episode was terminated by the first therapy. The rate of appropriate shock as well as inappropriate therapies was quite high compared to typical ICD cohorts. In particular T-wave oversensing seems to be challenging for the S-ICD detection algorithms also in this cohort. Funding Acknowledgement: Type of funding source: None